Development of Wordwall Learning Media Based on Student Characteristics in Sejarah Kebudayaan Islam at Madrasah Ibtidaiyyah - Wan Tasya Luthfiah Anwar; Siti Halimah; Haidir Haidir (Program Pascasarjana UMSB, 2026)
This study aims to develop and evaluate Wordwall based learning media tailored to student characteristics in Islamic Cultural History at Madrasah Ibtidaiyyah. By focusing on Wordwall learning media development, this research addresses the need for innovative digital tools in Islamic education. This research emploted the Research and Development (RD) method, following the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data were collected through observation, interviews, questionnaires, and tests, using both qualitative and quantitative analysis. Initial findings indicated a dominance of visual and kenaesthetics learning styles among students. The results of the study are as follows: 1) The development process successfully followed the five stages of the ADDIE model; 2) Expert validation yielded a score of 91.66% form both media and material specialists, categorising the media as “highly feasible”; 3) The effectiveness test showed significant improvement in student learning outcomes, with N-Gain scores in limited trials reaching 0.87 (87% effectiveness) for auditory/visual styles and 0.88 (88%) for kinaesthetic styles. In broader trials, N-Gain scores reached 0.93 (93%) for visual, 0.92 (92%) for auditory, and 0.86 (86%) for kinaesthetic styles, all falling within the “highly effective” category; 4) Practicality tests resulted in average scores of 3.5 from teachers and 3.4 from students, both classified as “higly practical”. It is concluded that the character based Wordwall media for the Sunan Kalijaga topic is a valid, practical, and highly effective tool for enhanching student learning outcomes in Madrasah Ibtidaiyyah.